THE EVOLUTION OF THE CALABRIAN ARC: EVIDENCE FROM PALEOMAGNETIC AND GPS OBSERVATIONS - Mattei M.; Cifelli F.; D'Agostino N. (My University, 2007)
The present-day arcuate shape of the Calabrian Arc has been accomplished during Neogene and Early Pleistocene by large and opposite vertical axis rotations along the two arms of the Arc. Clockwise (CW) rotations have been systematically registered in Sicily and Calabria, whereas counterclockwise (CCW) rotations were measured in Southern Apennines. Such opposite vertical axis rotations ceased in the uppermost part of the Lower Pleistocene (about 1 Ma ago) along almost the entire Calabrian Arc and are not observed in the present-day GPS velocity field. The end of the Calabrian Arc bending during the Quaternary marks a decrease in the efficiency of the tectonic processes related to the long-lived subduction of the Ionian slab, which caused the halting of the back-arc opening in the Southern Tyrrhenian Sea. © 2007 Elsevier B.V. All rights reserved.
Keywords: CALABRIAN ARC; GPS; PALEOMAGNETISM; SUBDUCTION; Neogene; Pleistocene; Cenozoic::Neogene; Кайнозой::Неоген; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен